2020
DOI: 10.3390/microorganisms8030436
|View full text |Cite
|
Sign up to set email alerts
|

Application of an O-Linked Glycosylation System in Yersinia enterocolitica Serotype O:9 to Generate a New Candidate Vaccine against Brucella abortus

Abstract: Brucellosis is a major zoonotic public health threat worldwide, causing veterinary morbidity and major economic losses in endemic regions. However, no efficacious brucellosis vaccine is yet available, and live attenuated vaccines commonly used in animals can cause human infection. N- and O-linked glycosylation systems have been successfully developed and exploited for the production of successful bioconjugate vaccines. Here, we applied an O-linked glycosylation system to a low-pathogenicity bacterium, Yersinia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…However, we found that the protection effect of the CTB‐based conjugate vaccines for O2 serotype of K. pneumoniae is not satisfactory as expected (Figure S4 , Supporting Information), [ 16 ] which might attribute to the weaker immunogenicity of its simple disaccharide repeat structure. In order to enhance immune response to this kind of polysaccharide antigens, a fully biosynthetic NP formed from proteinaceous monomers was used.…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…However, we found that the protection effect of the CTB‐based conjugate vaccines for O2 serotype of K. pneumoniae is not satisfactory as expected (Figure S4 , Supporting Information), [ 16 ] which might attribute to the weaker immunogenicity of its simple disaccharide repeat structure. In order to enhance immune response to this kind of polysaccharide antigens, a fully biosynthetic NP formed from proteinaceous monomers was used.…”
Section: Resultsmentioning
confidence: 69%
“…In previous studies, we successfully produced glycoconjugate vaccines in some attenuated pathogens. [ 16 ] The next step required a general host with low‐cost, ease of culture propagation, and scalability. The laboratory E. coli strain became a possibility.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A limitation in this study is the selection of hypovirulent strain B. abortus S19 as challenge strain for protection experiments [ 43 , 71 , 72 ]. B. abortus S19 was originally isolated as a virulent strain from a Jersey cow in 1923 and was found to become attenuated after being kept in the laboratory at room temperature for more than a year [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most widely used one is cholera toxin B subunit (CTB) [ 11 ], which acts as a well-known mucosal adjuvant [ 12 , 13 ]. Moreover, both protein and bacterial polysaccharide antigens can be displayed on the CTB via fusion expression or glycosylation, which significantly improves the antigen-specific immune response evoked by the antigens [ 14 , 15 , 16 , 17 ]. Another AB5 family member is shiga toxin B subunit (StxB), which is also used as a carrier for immune enhancement.…”
Section: Introductionmentioning
confidence: 99%